Clinical, dermoscopic, and histopathologic evaluation of vitamin C versus PRP, with microneedling in the treatment of mixed melasma: A split‐face, comparative study. Issue 2 (9th December 2021) - Abdel‐Rahman, Amal T.; Abdel‐Hakeem, Fatma G.; Ragaie, Maha H.
Abstract: Melasma is a common esthetic problem affecting the face with a lot of risk factors being incriminated. Although several treatment options are available, none of them is satisfactory. This split face prospective study aimed to compare the efficacy of microneedling with vitamin C versus with platelet‐rich plasma (PRP) in the management of mixed melasma. Ten females with bilateral mixed facial melasma were treated with six sessions of microneedling. After the needling vitamin C was applied on the right side of the face and PRP was applied on the left side. Clinical, dermoscopic, and histological assessment of the used treatments was done 1 month after the last session. The clinical and dermoscopic clearance of melasma was proved significantly on both sides of the face but was more significant with vitamin C ( P = 0.005). Reduction of epidermal melanin and dermal melanophages was more observed with vitamin C. Moreover, MART‐1 stain revealed a more significant reduction in the epidermal, dermal, and the total MART‐1 positive cells with vitamin C ( P = 0.044, 0.039, and 0.035, respectively). Microneedling with vitamin C was more efficient in treating mixed melasma than with PRP.